Growth performance and mineral analysis of Pleurotus ostreatus (oyster mushroom) cultivated on spent mushroom medium mixed with rubber tree sawdust (In press) - Fathie Ahmad, Zakil; Raffiza, Mohd Isa; Mohd Shafiq, Mohd Sueb; Ruzinah, Isha (Elsevier Ltd, 2022)
The objective of this paper is to study potential application of spent mushroom substrate (SMS) in production of Pleurotus ostreatus mushroom. A various mass ratio mixture of rubber sawdust (RS) and SMS with wheat bran supplement were prepared for mushroom cultivation. The mushroom house was kept at an optimal condition with temperature between 28 and 33 ℃ and humidity in the range between 80 and 95%. The results showed that the 50% SMS + 50% RS had a significantly higher of average total yield at 156.12 g/bag, biological efficiency (B.E) of 55.76% and required only 26 ± 2 days for mycelium growth in comparison to 100% RS, a control substrate. It is also found that potassium (K) was the most concentrated macro element and all heavy metal concentrations were below the maximum permitted by WHO/FAO in the first fresh mushroom collected. Therefore, it can be proven that SMS can be a great solution to the disposal issue, and it can be an excellent medium for the cultivation of Pleurotus spp. when it is combined with the RS